Mast Syndrome Outside the Amish Community: SPG21 in Europe - Amprosi, Matthias; Indelicato, Elisabetta; Nachbauer, Wolfgang; Hussl, Anna; Stendel, Claudia; Eigentler, Andreas; Gallenmüller, Constanze; Boesch, Sylvia; Klopstock, Thomas (Frontiers in Neurology, 2022)
1.1 Background Mast-syndrome is a rare disorder belonging to the group of the hereditary spastic paraplegias (HSP). It is caused by bi-allelic mutations in the ACP33 gene and has originally been described in Old Order Amish. Outside this population, only one Japanese and one Italian family have been reported. Herein, we describe five subjects from the first three SPG21 families of German and Austrian descent. 1.2 Methods Five subjects with a complicated HSP were referred to our centers. Work-up consisted of neurological examination, neurophysiological and neuropsychological assessments, MRI and genetic testing. 1.3 Results Onset varied from child- to adulthood. All patients exhibited predominant spastic para- or tetraparesis with positive pyramidal signs, pronounced cognitive impairment, ataxia and extrapyramidal signs. Neurophysiological work-up showed abnormal motor and sensory evoked potentials in all patients. Sensorimotor axonal neuropathy was present in one patient. Imaging exhibited thin corpus callosum and global brain atrophy. Genetic testing revealed one compound heterozygous and two homozygous mutations in the ACP33 gene. 1.4 Conclusion Herein we report the first three Austrian and two German patients with SPG21, presenting a detailed description of their clinical phenotype and disease course. Our report adds to the knowledge on this extremely rare disorder and highlights that SPG21 must be considered in the differential diagnosis of complicated HSP also outside the Amish community.